Translation to Bundle Operators - Thomas P. Branson; Doojin Hong (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We give explicit formulas for conformally invariant operators with leading term an $m$-th power of Laplacian on the product of spheres with the natural pseudo-Riemannian product metric for all $m$.